2010
DOI: 10.1177/0956247809362842
|View full text |Cite
|
Sign up to set email alerts
|

Migration and environment in Ghana: a cross-district analysis of human mobility and vegetation dynamics

Abstract: Migration—environment linkages are at the centre of media attention because of public concern about climate change and a perceived “flooding” of migrants from less developed countries into more affluent parts of the world. In the past few years, a substantial body of conceptual literature about environmentally induced migration has evolved, but there is still a paucity of empirical work in this area. Moreover, the environmental causes of migration have been studied largely in isolation of the environmental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…Specifically, in the forest-savanna transition zone of Ghana, both Leach and Fairhead (2000) and Adjei-Nsiah et al (2004) illustrate the mechanisms by which migrant farmers in the region negatively affect forest cover, long-term soil fertility, and fallow management. However, this has been contested more recently, as little land-use change has been reported in this destination region, presumably due to a lack of land access for migrant farmers (van der Geest et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, in the forest-savanna transition zone of Ghana, both Leach and Fairhead (2000) and Adjei-Nsiah et al (2004) illustrate the mechanisms by which migrant farmers in the region negatively affect forest cover, long-term soil fertility, and fallow management. However, this has been contested more recently, as little land-use change has been reported in this destination region, presumably due to a lack of land access for migrant farmers (van der Geest et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, within the period of 1995-2000, approximately 1.4 million people changed their district of residence (Ghana Statistical Service 2002). Various studies on migration in Ghana (e.g., Kasanga and Avis 1988, Nabila 1992, Tutu 1995, Anarfi et al 2003, Litchfild and Waddington 2003, Ackah and Medvedev 2010, van der Geest et al 2010) emphasize migration from the north to the central forest-savanna transition zone and coastal areas of the country as an important component of people's livelihood strategies. What is certain from empirical and theoretical research on migration, in all its varieties, is that environmental change is one of the many contributing factors, and environment-migration relationships are complex (Rocheleau et al 1996, Carr 2005, Jonsson 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are devising a numbers of ways to link multiple types of data in order to assess and anticipate environmental migration. In Ghana, Van der Geest et al (2010) link census data to vegetation data to examine the connections between internal migration and vegetation dynamics. Feng et al (2010) examine the connection between crop yields and migration by merging crop data with census data.…”
Section: Forced Displacementmentioning
confidence: 99%
“…Taking the relationship between off-farm employment and ecosystem as an example, some researchers believe that laborers leaving the rural areas alleviates the pressures on land, and thereby contributes to the deforestation reduction, biodiversity conservation and local environmental protection (Rodríguez-Meza et al, 2004;Van der Geest et al, 2010;Wang et al, 2011). The experiences in some areas, especially in the remote mountainous areas of North America and some parts of Europe, showed that off-farm employment of rural laborers contributes to the forest transition and re-growth (Caraveli, 2000;Rudel et al, 2005;Gellrich and Zimmermann, 2007;Izquierdo et al, 2011;Li and Zhao, 2011).…”
mentioning
confidence: 99%